Evaluation of Whether Emergency Physicians Should Join the Multidisciplinary Team for Older Hip Fracture Patients - Guan, Lan; Wang, Cong; Zhao, Bin; Yang, Minghui; Zhu, Shiwen; Wu, Xinbao (Frontiers in Surgery, 2022)
Background: Geriatric hip fracture is one of the most common end-stage events in older patients with osteoporosis. We aimed to improve the original co-management process by engaging emergency physicians in the preoperative multidisciplinary management team (MDT). We evaluated this intervention in terms of reducing patient waiting time before surgery. Methods: Emergency Department data and hospitalization data for patients diagnosed with geriatric hip fractures in Beijing Jishuitan Hospital (JSTH) were collected and sorted into the intervention group, for whom the MDT included emergency physicians (from January 2019 to December 2019), and the control group (from January 2017 to December 2017). The percentage of patients treated with surgery within 48 hours of admission was used as the primary outcome. The secondary outcomes included the percentage of patients receiving surgical treatment after admission, the rate of perioperative medical complications during hospitalization, postoperative admission to the Intensive Care Unit, and total deaths during hospitalization. Results: A total of 2152 patients were enrolled. The rate of hypertension (58.5% vs 52.1%), coronary heart disease (24.6% vs 19.9%), and cerebrovascular disease (19.4% vs 15.5%) was higher in the intervention group than in the control group. The percentage of patients receiving surgical treatment in the intervention group (98.3%) was significantly higher than in the control group (96.3%, p = 0.004). The proportion of patients receiving surgical treatment within 48 hours of admission was significantly higher in the intervention group (82.4%) than in the control group (60.4%, p < 0.001). The hospital stay was significantly shorter in the intervention group compared with the control group (p < 0.001). The incidence of perioperative medical complications and mortality during hospitalization was similar in the two groups. Conclusions: Involving emergency physicians in the MDT can reduce the waiting time before surgery and the hospital stay for older hip fracture patients.